STUDI PENGARUH TEKANAN OPERASI DAN KOMPOSISI BAHAN PENYUSUN TERHADAP PERMEABILITAS MEMBRAN ULTRAFILTRASI UNTUK - Nita Kusumawati, (Matematika dan Sains, 2010)
Detergent is a kind of liquid waste who can give a dangerous effect to environment. The increasing of detergent uses can make eutrofication effect that can block the sunsine dan decrease O2 in the water. A conventional Detergent waste treatment that have been doing all this time, such as aeration, adsorption with active carbon or bentonite and coagulation with salt of carbonate and sulfate give unstatisfied result cause of small reduction power and high operational cost. Because of that, membrane technology hoped can be alternative technology which is easier and cheaper for detergent separation. In this experiment, the ultrafiltration membrane is made of chitosan that was dissolved in formic acid with variation composition of chitosan 1-3 gram in 100 mL of solvent which after that the membrane was applicated to